ADOLESCENT IDIOPATHIC SCOLIOSIS (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Adolescent Idiopathic Scoliosis (AIS) is considered as a complex, three-dimensional structural deformity of the spine, occurring in the transition from childhood to skeletal maturity. This review synthesizes data from leading global authorities (SRS, USPSTF, SOSORT) and seminal investigators such as Weinstein, Lenke, and Negrini, analyzing the pathology through the lens of neurophysiological dysregulation, genetic determinism, and biomechanical progression. The review emphasizes the importance of early detection and the effectiveness of evidence-based non-operative and operative interventions in preventing long-term pulmonary and psychosocial complications.
Keywords: Adolescent, idiopathic, scoliosis, AIS, teenage, deformity, vertebrae, spine, curve, degree, cobb angle, painless, bracing, screening, surgical intervention, physical therapy.